Case series of high-grade soft tissue sarcoma of the lower limb with delayed diagnosis: Experience at a tertiary hospital in northern Tanzania. (August 2022) - Lodhia, Jay; Goodluck, Gregory; Tendai, Joylene; Urassa, Ellyagape; Nkya, Gilbert; Mremi, Alex
Abstract: Introduction and importance: Soft tissue sarcoma is an uncommon form of cancer with poor prognosis. Early diagnosis and treatment are vital for improving the treatment outcomes. Case presentation: We report a series of high-grade soft tissue sarcomas of the lower extremity with delayed diagnosis to gain insight into the presentation, treatments and outcomes for this rare disease and to determine whether limb-salvage surgery yields reasonable outcomes. Clinical discussion: Timely health seeking has an impact on the outcome of the treatment of any particular disease. Patient delays are usually socio-economic factors. Soft tissues sarcomas are uncommon malignant tumors that even managed adequately have a poor 5-year survival. Limb salvage becomes questionable especially when patients present late with adverse symptoms. Conclusion: In this series, we found that patients presented late and this led to unfavorable oncological outcomes, also limb salvage was not an option due to delayed presentation. Thus, early diagnosis is recommended so as to improve treatment outcome.